2015
DOI: 10.1163/15685411-00002923
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pesticides, soil temperature and moisture on entomopathogenic nematodes from southern Benin and control of underground termite nest populations

Abstract: The influence of three pesticides on the viability and infectivity of four Beninese isolates of entomopathogenic nematodes (EPN), Heterorhabditis indica Ayogbe1, H. sonorensis Azohoue2, H. sonorensis Ze3, and Steinernema sp. Bembereke, was determined. The impact of both soil temperature and soil moisture on the virulence of these EPN to Trinervitermes occidentalis was investigated in laboratory assays. The effect of EPN-infected Galleria mellonella larvae on underground populations of Macrotermes bellicosus wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…But this method showed limitations as comeback is experienced after a period of time for some groups of termites that are capable of grooming new queen and king (Cubitermes and Macrotermes). Other nonchemical termite control methods include botanical termiticides [43], intercropping, crop rotation, planting of resistant crops [44], physical methods, i.e., debris removal, mechanical barriers, heat, high voltage electricity or electrocution, wood replacement, and biological control, i.e., use of predators [45], biological control agents such as fungi [46], bacteria, and nematodes [31,35]. In a partial review, Myles [47] reported 2 viruses, 5 bacteria, 17 fungi, 5 nematodes, and 4 mites that have the potential to kill termites; the full list of these organisms being no doubt larger.…”
Section: Methods Of Control Of Termitesmentioning
confidence: 99%
See 4 more Smart Citations
“…But this method showed limitations as comeback is experienced after a period of time for some groups of termites that are capable of grooming new queen and king (Cubitermes and Macrotermes). Other nonchemical termite control methods include botanical termiticides [43], intercropping, crop rotation, planting of resistant crops [44], physical methods, i.e., debris removal, mechanical barriers, heat, high voltage electricity or electrocution, wood replacement, and biological control, i.e., use of predators [45], biological control agents such as fungi [46], bacteria, and nematodes [31,35]. In a partial review, Myles [47] reported 2 viruses, 5 bacteria, 17 fungi, 5 nematodes, and 4 mites that have the potential to kill termites; the full list of these organisms being no doubt larger.…”
Section: Methods Of Control Of Termitesmentioning
confidence: 99%
“…Ten species of termites were found associated with citrus orchards in Benin: Amitermes guineensis, Ancistrotermes crucifer, Angulitermes truncates, Coptotermes intermedius, Cubitermes sp., M. bellicosus, Microcerotermes progrediens, Pericapritermes sp., Trinervitermes occidentalis, and Trinervitermes trinervius [30]. Among these, M. bellicosus, a fungus-growing termite, is the most important species that undermines citrus production and T. occidentalis, a grass-feeder termite, the most important to maize, cassava, groundnut, and bean grown under citrus canopies [31]. Abe et al [2] also reported that the most troublesome termites in agriculture are the fungus-growing termites.…”
Section: Classification and Distribution Of Termitesmentioning
confidence: 99%
See 3 more Smart Citations